Researcher creations?: The positioning of policy texts in higher education research - Ashwin, Paul; Smith, Karen (Higher education, 2015)
In this article we explore the way in which policy texts are positioned in a selection of higher education journal articles. Previous research has suggested that policy implementation studies have taken an uncritical approach to researching policies. Based on an analysis of articles published in higher education and policy journals in 2011, we argue that whilst these criticisms do appear to be valid, there is a bigger problem with the ways that policy texts are analysed and used in higher education research. This is that rather than subjecting particular policy texts to a sustained analysis, the majority of articles appear to focus on having an impact on policies that are very broadly conceived. We explore the implications of this and conclude by calling for more sustained, in-depth, analytical and critical research into the development and impact of higher education policies on higher education practices.